Pharmaceutical evaluation of compounded furosemide capsules and excipient performance - Pabllo Adelino Estevam Barbosa; Roberto Bentes Rozário; Tatiane Pereira de Souza; Kátia Solange Cardoso Rodrigues dos Santos (Universidade de São Paulo, 2022)
Abstract Compounding pharmacies play an important role not only in compounding personalized formulations, but also preparing drugs at the same concentration and dosage as those from commercial manufacturers. The excipients used in compounding are generally standardized for many drugs, however they do not consider the intrinsic properties, such as the poor water solubility, of each substance. The excipient performance of commercially available compounded furosemide capsules in 7 compounding pharmacies from Manaus was evaluated and compared them to the performance of the reference medicinal product (Lasix® tablets) and 2 batches of capsules made in-house (T2 and T4) with a standardized excipient. All batches were subjected to tests for weight variation, assay, uniformity of dosage units, disintegration and dissolution profile. Of the 7 different compound formulas acquired in the compounding pharmacies, only 2 passed all tests. Most formulas passed the tests for weight determination, disintegration time and assay, however batches from 2 establishments failed in regards to the uniformity of the content and 5 batches failed the dissolution test. The reference medicinal product was approved in all tests, as were the T2 capsules made in-house with drug-excipient ratio 1:2. These results confirm the importance of the excipient composition, especially for poorly soluble drugs.